Implementation of Non-Pharmacology on Post-Partum Mothets at Independent Practice Office of Midwife - Indrayani, Triana; Herlina, Novia (GLOBAL HEALTH SCIENCE GROUP, 2024)
Exclusive breastmilk (ASI) is the breastmilk that is given to newborn without any additional food or liquid such as formula milk, orange juice, and water before the newborn ages 6 months. Several factors can cause the breastmilk production is not smooth, such as nutritional factor, baby sucking factor, breast maintenance, psychological factor, knowledge factor, and socio-cultural factor. One of the efforts to overcome the issues is by providing non-pharmacology care such as woolwich massage. This research aims to know the effect of woolwich massage on breastmilk production. In this case, the method applied is Pretest-Posttest without Control Group Design. The population involved in this research is 20 post-partum mothers with normal labor, which were further chosen as the research samples through total sampling. Furthermore, this study was carried out in December 2023. The intervention carried out since the first day to the third day is the woolwich massage that was given twice a day (morning and afternoon) for ± 15 minutes. In this case, the instrument used was observation sheet, electric breastmilk pump, and measuring cup. Data analysis was further done through univariate analysis and bivariate analysis using dependent t-test. Woolwich massage affects the production of breastmilk.